2014
DOI: 10.1002/ajpa.22536
|View full text |Cite
|
Sign up to set email alerts
|

Birth is but our death begun: A bioarchaeological assessment of skeletal emaciation in immature human skeletons in the context of environmental, social, and subsistence transition

Abstract: The second millennium BC was a period of significant social and environmental changes in prehistoric India. After the disintegration of the Indus civilization, in a phase known as the Early Jorwe (1400-1000 BC), hundreds of agrarian villages flourished in the Deccan region of west-central India. Environmental degradation, combined with unsustainable agricultural practices, contributed to the abandonment of many communities around 1000 BC. Inamgaon was one of a handful of villages to persist into the Late Jorwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 106 publications
(208 reference statements)
1
15
0
Order By: Relevance
“…The authors found that immature femora show alteration in cross‐sectional bone shape that is consistent with the acquisition of locomotor behavior, as indicated by previous studies of ontogenetic changes noted earlier (Schug and Goldman, ). However, children during the first 10 years of life with low BMI, also show reduced compact bone mass consistent with a significant increase in cortical bone porosity (Schug and Goldman, ).…”
Section: Bone Strength Maintenance and Loss Over The Life Coursesupporting
confidence: 75%
See 3 more Smart Citations
“…The authors found that immature femora show alteration in cross‐sectional bone shape that is consistent with the acquisition of locomotor behavior, as indicated by previous studies of ontogenetic changes noted earlier (Schug and Goldman, ). However, children during the first 10 years of life with low BMI, also show reduced compact bone mass consistent with a significant increase in cortical bone porosity (Schug and Goldman, ).…”
Section: Bone Strength Maintenance and Loss Over The Life Coursesupporting
confidence: 75%
“…The authors suggest that biomechanical strain may still have been sufficient in the early Neolithic despite systemic stress affecting growth (Temple et al, ). A study by Schug and Goldman () also attempted to examine midshaft femoral bone morphology along with another indicator of bone turnover in the study of stress in a second millennium BC prehistoric sample of immature skeletons from India. The authors found that immature femora show alteration in cross‐sectional bone shape that is consistent with the acquisition of locomotor behavior, as indicated by previous studies of ontogenetic changes noted earlier (Schug and Goldman, ).…”
Section: Bone Strength Maintenance and Loss Over The Life Coursementioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent call to revitalize the way in which we interpret “health” and “stress” suggests that we should seek to implement a more comprehensive approach, and potentially pursue new avenues of research (Klaus, 2014; Temple and Goodman, 2014). While previous growth studies have relied on long bone length, more recently, other skeletal parameters such as cortical thickness, or compact bone geometry and histology, have provided fruitful new avenues for investigation (Mays et al, 2009; Robbins and Goldman, 2014). This study aims to add to this developing corpus by introducing non‐adult vertebral dimensions as a new method of detecting growth disruption in past populations.…”
mentioning
confidence: 99%